A Review on Sentiment Analysis and Visualization of Customer Reviews (International Journal of Engineering and Computer Science, 2015)
The Web has become an excellent source for gathering consumer opinions. There are now numerous Web sites containing such opinions, e.g., customer reviews of products, forums, discussion groups, and blogs. All these reviews are the opinions of people all over the world about different products. With the growing availability and popularity of opinion-rich resources such as review forums for the product sold online, choosing the right product from a large number of products have become difficult for the user. These sources are underutilized both by consumers and businesses due to their unstructured nature, serial presentation, limited search tools, and low ratio of useful information to the overall amount of data. The proposed system illustrates visual analysis system that performs sentiment analysis and derives insight from a collection of online reviews of products from customer.  Effective visual analysis of online customer opinions is needed, as it has a significant impact on building a successful business and helps the customers in decision making process. This paper presents background Study of Sentiment Analysis or Opinion Mining and gives overview of proposed methodology with insights into past research work.